2011
DOI: 10.1016/j.bcp.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Critical selection of reliable reference genes for gene expression study in the HepaRG cell line

Abstract: The human HepaRG cell line has shown to be a valuable in vitro tool for repeated exposure to chemical compounds and to evaluate their potential toxic outcome. Seen the importance given by the actual EU legislation of cosmetics and chemical substances to the use of in vitro methods in human safety evaluation, one can expect that HepaRG cells will gain importance as human-relevant cell source. At the transcriptional level, RT-qPCR assays are often used to obtain quantitative results. The choice of internal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
(21 reference statements)
2
23
0
Order By: Relevance
“…However, no reference was provided. Moreover, neither of these reference genes were determined to be proper internal controls in HepaRG in our previous experiments (6 ). In one report, no proof of normalization was described at all (see online Supplemental Table 1 for reference).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no reference was provided. Moreover, neither of these reference genes were determined to be proper internal controls in HepaRG in our previous experiments (6 ). In one report, no proof of normalization was described at all (see online Supplemental Table 1 for reference).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…RPS18 was used as a single reference gene in almost half of the studies, but in our study it was found to be less valuable or even useless as an internal control in the HepaRG cell line. RPS18 was listed at the bottom of the ranking in geNorm, BestKeeper, and NormFinder, and according to BestKeeper it was not fit at all as a reference gene for use with differentiating and differentiated HepaRG cells (6 ). However, the most critical issue to be argued is that the RPS18 gene was used as an internal control without any evidence of its expression stability in HepaRG in the described experimental design.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only three published papers investigated the expression stability of common ERG to normalize the qPCR expression of genes involved in AD (Gutala and Reddy, 2004;Barrachina et al, 2006;Coulson et al, 2008). Among these reports, only one was performed with the SYBR Green chemistry (Gutala and Reddy, 2004), and none compared the expression stability of their selected ERGs with different mathematical algorithms, as it has been performed in other biological contexts (Ceelen et al, 2011). Therefore, the first purpose of the present work was to identify a robust set of ERGs for mRNA profiling in AD frontal cortex tissue.…”
Section: Introductionmentioning
confidence: 95%
“…For these reasons, it is expected that the use of HepaRG cells will gain global application as a human-relevant cell model. Ceelen et al has presented optimal reference genes for gene expression analyses in HepaRG progenitor cells undergoing differentiation with 2% dimethylsulfoxide (DMSO), where significant phenotypic and molecular changes occurred with time [12]. However, similar studies in fully differentiated HepaRG cells maintained in culture have not yet been published.…”
Section: Introductionmentioning
confidence: 99%